Development of Disruptive Open Access Journals - Anderson, Terry; McConkey, Brigette (Canadian Journal of Higher Education, 2010)
Open access (OA) publication has emerged, with disruptive effects, as a major outlet for scholarly publication. OA publication is usually associated with on-line distribution and provides access to scholarly publications to anyone, anywhere–regardless of their ability to pay subscription fees or their association with an educational institution. The article overviews the growth and impact of OA publication in Canada and elsewhere. The article also presents a case study of the evolution over its first nine years of the International Review of Research in Open and Distance Education (IRRODL). IRRODL has become the most widely read and widely cited journal in the distance education and open learning community, yet it continues to struggle for recognition by some academics, funding, and rating organizations. In this article IRRODL’s editors document the challenges involved in leading the charge for equal support for open access journals from Canada’s research funding organizations and for review and accreditation from commercial and non-commercial review services. In its literature review section the article looks at scholarly works documenting and comparing on-line journals to ones that publish in paper only, or in which access is restricted behind the walls of licensed use. The article also documents issues related to various innovations, including production of articles in both text and audio formats, and the challenges of incorporating more interactive media into a scholarly, peer- reviewed journal. Data is produced demonstrating the ways in which 72 CJHE / RCES Volume 39, No. 3, 2009 influence and impact for open access journals can be measured, including hit rates and citations reference data from Google Scholar. The article concludes with a description and discussion of the advantages and challenges of using review and publication management tools such as Open Journal System in the production of open access journals.